Antiproton tagging and vertex fitting in a Timepix3 detector - Aghion, Stefano; Müller, Simon R.; Oberthaler, Markus K.; Zimmer, Christian; Demetrio, Andrea (Journal of Instrumentation, 2018)
Studies of antimatter are important for understanding our universe at a fundamental level. There are still unsolved problems, such as the matter-antimatter asymmetry in the universe. The AEgIS experiment at CERN aims at measuring the gravitational fall of antihydrogen in order to determine the gravitational force on antimatter. The proposed method will make use of a position-sensitive detector to measure the annihilation point of antihydrogen. Such a detector must be able to tag the antiproton, measure its time of arrival and reconstruct its annihilation point with high precision in the vertical direction. This work explores a new method for tagging antiprotons and reconstructing their annihilation point. Antiprotons from the Antiproton Decelerator at CERN were used to obtain data on direct annihilations on the surface of a silicon pixel sensor with Timepix3 readout. These data were used to develop and verify a detector response model for annihilation of antiprotons in this detector. Using this model and the antiproton data it is shown that a tagging efficiency of 50± 10% and a vertical position resolution of 22 ± 0.5 μm can be obtained.
Gesehen am 03.05.2019